Dietary supplementation of coffee pulp extract enhances growth performance and intestinal morphology in broiler chicken - Kiattisak Huanhong; Chompunut Lumsangkul; Chaiwat Arjin; Sasithorn Sirilun; Tibet Tangpao; Yu-Lei Wang; Raktham Mektrirat; Chen-Si Lin; Sarana Rose Sommano; Korawan Sringarm (Poultry Science)
ABSTRACT: Coffee is a renowned beverage derived from plants globally. In the coffee production process, coffee pulp is a by-product that is abundant in phenolic compounds. Therefore, this study aimed to assess the effect of coffee pulp extract (CPE) on growth performance, blood biochemistry, intestinal morphology, carcass characteristics, and meat quality of broiler chickens. A total of 160 one-day-old male Ross 308 broilers were randomly allocated to four treatments with five replicates and eight chicks per replicate in a completely randomized design. These four dietary treatments included a basal diet with CPE of 0 (Control), 250 (CPE250), 500 (CPE500), and 1,000 (CPE1000) mg/kg diet for 35 days. The results showed that the body weight (BW) of the CPE500 group was significantly higher (P < 0.01) compared to the other groups at 35 days. Moreover, CPE500 increased the average daily gain (ADG) (P = 0.004) and reduced the feed conversion ratio (FCR) (P = 0.008). No significant differences (P > 0.05) were observed in the blood biochemistry profile. In addition, the investigation on intestinal morphology showed that CPE supplementation enhanced villus height (VH) (P = 0.004), crypt depth (CD) (P < 0.05), and ratio of VH:CD (P < 0.05) in the duodenum. Dietary supplementation with CPE significantly increased the percentage of neck weight (P < 0.05) compared to the control groups. However, no significant effects of CPE supplementation were observed on the meat quality parameters of breast and thigh muscles, including pH, color, water-holding capacity, and tenderness (P > 0.05). A significant increase (P < 0.05) in thigh fat content was observed with CPE supplementation. In conclusion, CPE500 can improve the growth performance and intestinal morphology of broiler chickens despite the presence of antioxidants and anti-inflammatory agents. This suggests that coffee pulp biomass could potentially be used as an alternative feed additive from agricultural biomass in broiler production.